Frontispiece: Zeolite‐Based Organic Synthesis (ZeoBOS) of Acortatarin A: First Total Synthesis Based on Native and Metal‐Doped Zeolite‐Catalyzed Steps. Issue 7 (31st January 2017) - Wimmer, Eric; Borghèse, Sophie; Blanc, Aurélien; Bénéteau, Valérie; Pale, Patrick
Abstract : Zeolite‐Based Organic Synthesis (ZeoBOS) This new concept is described for the efficient access to structurally complex and functionalized molecules and illustrated with the total synthesis of acortatarin A, a unique antioxidant natural product. In this concept, organic synthesis could be performed by using zeolites, native or metal‐doped, as heterogeneous catalysts in a way similar to the well‐known polymer‐supported assisted synthesis. The total synthesis of acortatarin A was achieved through a novel strategy, based on several synthetic steps catalyzed by H‐ or metal‐doped zeolites as catalysts. Notably, copper‐doped zeolite and silver‐doped zeolite provided the two key steps of this synthesis, that is a new yne–pyrrole coupling reaction and the spiroketalization of an alkyne diol. For more details see the Communication by P. Pale et al. onpage 1484 ff.